2017
DOI: 10.18235/0000801
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Social Media on Gender in Latin America

Abstract: , summarizes the relevant social media analysis methodology and reports the results of a pilot study to understand and describe communication related to gender issues on Facebook, Twitter, and blogs in Argentina, Brazil, Colombia, Guatemala, and Mexico. The pilot was conducted over a month-long period in November and December of 2015. This Technical Note analyzes the timing, content, and network structure of the captured communications from each country. It finds that social media can be a valuable communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Therefore, the existence of social networks in banks should allow them to interact with financial institutions using their digital devices. Batista et al (2017) confirm that the internet enables individuals to connect and express themselves as never before, and this connectivity and access to information profoundly changes power structures and, potentially, society itself. This study tries to explore how users or customers, especially women, benefit from social media and how it helps them to feel more empowered.…”
Section: Introduction 11 Backgroundmentioning
confidence: 77%
“…Therefore, the existence of social networks in banks should allow them to interact with financial institutions using their digital devices. Batista et al (2017) confirm that the internet enables individuals to connect and express themselves as never before, and this connectivity and access to information profoundly changes power structures and, potentially, society itself. This study tries to explore how users or customers, especially women, benefit from social media and how it helps them to feel more empowered.…”
Section: Introduction 11 Backgroundmentioning
confidence: 77%
“…This scholarship has often focused on public debates (Batista et al, 2017; Harlow, 2017; Long, 2018; Senmartin, 2014) and voting practices (Bolgov et al, 2017; Filer & Fredheim, 2017; Navia & Ulriksen Lira, 2017; Rincón, 2011).…”
Section: Usesmentioning
confidence: 99%
“…Scholarship on politicians and government agencies has concluded that their use of platforms, particularly during election campaigns, has been pervasive (Batista et al, 2017; Corrales Mejías, 2015; Filer & Fredheim, 2017; Rincón, 2011; Santana & Huerta Cánepa, 2019). A report by Transparencia Electoral about Paraguay’s 2018 elections noted that “although the law provides free [media] spaces for parties to communicate their proposals to the electorate, the majority preferred to transmit their campaign messages through social media” (Transparencia Electoral en América Latina, 2018, p. 20).…”
Section: Actorsmentioning
confidence: 99%
“…Otra de las áreas es la de turismo (Amaro;Duarte, 2017;Brogueira;Batista;Carvalho, 2016;Martínez-Rolán et al, 2019). Marques y Koven (2017) estudian el uso de un grupo de Facebook sobre la diáspora portuguesa en Francia; lo hacen desde una perspectiva que combina "el estudio de narrativas online como prácticas sociales y el estudio lingüístico antropológico de comunidades imaginadas" 2 (p. 286).…”
Section: Serraunclassified